Development Value Stream Mapping to Identify 8 Types of Waste - Sahdhani, Muhammad Arkan; Karningsih, Putu Dana; Dewi, Dyah Santhi; Sahlan (Tibuana, 2025)
This study proposes an Extended Value Stream Mapping (Extended VSM) framework to address the limitations of traditional VSM in identifying all eight types of waste (Muda), particularly those associated with human factors, environmental conditions, and material movement. While conventional VSM effectively maps value-added and non-value-added activities, it often fails to detect motion waste, transportation inefficiencies, and underutilized human potential. The proposed framework integrates time measurement using Stopwatch Time Study (STS), workflow analysis through the Flow Process Chart (FPC), ergonomic risk evaluation with the Rapid Entire Body Assessment (REBA), mental workload assessment via NASA Task Load Index (NASA-TLX), and environmental condition indicators such as lighting, temperature, and noise. Designed for labor-intensive production systems, Extended VSM offers a multidimensional mapping tool capable of supporting continuous improvement initiatives. Although this research does not include a real-case implementation, the framework is designed to be practically applicable and empirically validated in future studies.